Would it be ethical to use motivational interviewing to increase family consent to deceased solid organ donation?. Issue 1 (14th October 2013) - Black, Isra; Forsberg, Lisa
Abstract : We explore the ethics of using motivational interviewing (MI), an evidence-based, client-centred and directional counselling method, in conversations with next of kin about deceased solid organ donation. After briefly introducing MI and providing some context around organ transplantation and next of kin consent, we describe how MI might be implemented in this setting, with the hypothesis that MI has the potential to bring about a modest yet significant increase in next of kin consent rates. We subsequently consider the objection that using MI in this context would be manipulative. Although we cannot guarantee that MI would never be used in a problematically manipulative fashion, we conclude that its use would, nevertheless, be permissible as a potential means to increase next of kin consent to deceased solid organ donation. We propose that MI be trialled in consent situations with next of kin in nations where there is widespread public support for organ donation.